Current Views of Torque Teno Virus (TTV) in Liver Diseases - I. V. Maev; T. I. Karlovich; A. I. Burmistrov; I. A. Chekmazov; D. N. Andreev; V. I. Reshetnyak (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. We review published evidence on the torque teno virus (TT virus, TTV), which was discovered in the late of the 20th century.Key points. TTV is frequently confirmed in patients with hepatitises of viral origin or no definite viral aetiology, as well as in healthy people. Particular biochemical and histological changes in hepatic tissue and bile duct epithelium are reported for TTV monoinfection, which suggest viral replication in hepatocytes. At the same time, no cytopathic effects inherent in pathogenic hepatotropic viruses were revealed in hybridisation assays with TTV-infected cells. Novel data incited novel opinions on the TTV interaction with human. Earlier views of hepatotropic TTV gradually changed with newer evidence on its dispersion and coinfection with other viruses, including known hepatitis agents. Polytropism of TTV disproves its exclusive attribution to hepatitis viruses. High prevalence of the virus in human population argues in favour of its non-pathogenic persistence in the human viriome. TTV DNA content in blood is proposed as an endogenous immune status marker to observe prior to organ transplantation.Conclusion. High TTV dispersion in human population suggests its persistence in the human viriome. Seldom observed damaging effect of TTV on hepatic cells and bile duct epitheliocytes may indirectly suggest its opportunistic pathogenic properties.